AN ANALYSIS ON THE LEARNERS’ NEEDS OF ENGLISH FOR SPECIFIC PURPOSES AT SMK TRI GUNA BHAKTI SURABAYA (RETAIN, 2013)
Abstrak Penelitian ini bertujuan untuk mendeskripsikan kebutuhan siswa akuntansi SMK Tri Guna Bhakti Surabaya dalam belajar bahasa Inggris serta materi pembelajaran Bahasa Inggris untuk mereka. Penelitian ini dirancang sebagai penelitian deskriptif qualitataive dengan kuisioner dan cek list observasi sebagai instrumen dalam pengumpulan data. Hasil dri penelitian ini menunjukkan bahwa siswa akuntansi SMK Tri Guna Bhakti Surabaya membutuhkan materi belajar Bahasa Inggris yang lebih spesifik khususnya yang sesuai dengan jurusan akuntansi. Namun, materi pembelajaran Bahasa Inggris yang diperuntukkan bagi mereka masih materi Bahasa Inggris umum. Kata Kunci: kebutuhan, siswa akuntansi, Bahasa Inggris untuk tujuan spesifik. Abstract This study is conducted to describe the accounting students’ of SMK Tri Guna Bhakti needs in learning English and the English teaching and learning materials for them. This study was designed as descriptive qualitative research with questionnaire and observation checklist as the instruments in obtaining the data. The results of the study showed that the needs of the accounting students of SMK Tri Guna Bhakti Surabaya is the more specific English teaching and learning materials for accounting study program but unfortunately, those students are still provided with general English teaching and learning materials. Keywords: needs, accounting students, English for Specific Purposes. Introduction Learners’ needs analysis is often described as the first step that the curriculum or course planners should do to determine the learners’ skills, competences, knowledge, needs and purposes in learning. This step helps the curriculum planners or learning provider know whether the content of the courses is relevant with the learners’ needs or not. Furthermore, according to Richards (2001:33), learners’ needs in English for Specific Purposes (ESP) are described in terms of performance, that is, in terms of what the learner will be able to do with the language at the end of a course of study. In many cases, learners’ needs may be relatively easy to determine, particularly if learners need to learn a language for very specific purposes, for example, employment in fields such as tourism, nursing, engineering or the hotel industry (Richards, 2001:53-54). Richards (2001:52) further says that needs analysis in language teaching may be used for a number of different purposes. For example, to find out what language skills a learner needs in order to perform a particular role, such as sales manager, or tour guide; to identify a gap between what students are able to do and what they need to be able to do; to collect information about a particular problem learners experience; to determine which students from a group are most in need of training in particular language skills, and to identify a change of direction that people in reference group feel is important. Needs itself, are often described in terms of a linguistic deficiency, that is, as describing the difference between what the learners can presently do in a language and what the learners should be able to do. What are identified as needs depends on a judgement and reflects the interest and values of those making such a judgement. Teachers, learners, employers, parents, and other stakeholders may thus have different views as to what needs are. Conelly and Clandinin (1988:24) define a stakeholder as a person or people with a right to comment on, and have input into, the curriculum process offered in schools. Different stakeholders may want different things from the curriculum. In addition, Brindley (1984) says, “The term need is not as straightforward as it might appear, and hence the term is sometimes used to refer to wants, desires, demands, expectation, motivations, lacks, constraints, and requirements”. In an educational setting, a learners’ needs analysis helps students identify where they are in terms of their knowledge, skills and competences, versus where they wish to be and their learning goals. It is related to the statement that adults learn better when they can see a reason why they are following a program of study and find the relevance between their purpose in learning and the content of the study that they must learn. Based on the researcher’s experience in teaching English to engineering students of SMKN 12 Surabaya, students have less motivation to learn English. Some of the students said that they do not see any relevance between their needs in learning English as engineering students and what they must learn from the textbook. The content of the textbooks for the all study programs in this school are mostly the same. Meanwhile, the students’ needs of each study program in learning Eglish are significantly different. Accounting students for example, they have to learn the process of summarizing, analyzing, and also reporting financial transactions. Here, the accounting students need to learn English as a part of those accounting activities. As an example, they find many vocabularies of finance in English and they have to know the meaning of all those words in order to understand or present a financial report. In this case, English becomes a means of those students activities in the subject area of finance so they have to learn English in more specific area, that is, accounting. This reality has inspired a variety of ESP course designs to address them. A basic ESP philosophy is to cater to specific needs of learners as much as possible (Robinson, 1991). It might be appropriate to say that no ESP courses should be conducted without needs analysis (Kaewpet, 2009). Based on those explanations above, the researcher is interested in conducting a learners’ needs analysis of ESP at SMK Tri Guna Bhakti Surabaya. As stated by Linse (1993), “It is the school’s responsibility to take into account the cultural, political, and personal characteristics of students as the curriculum is developed in order to plan activities and objectives that are realistic and purposeful.” Here, the researcher wants to know whether the English teaching and learning materials for the accounting students in this school are relevant with the needs of those students in learning English or not. The results of this study will be reported to the English teachers of SMK Tri Guna Bhakti Surabaya as suggestions to design specific materials for the accounting students. Based on the background of the study above, the research questions are formulated as follows. What are the needs of the accounting students at SMK Tri Guna Bhakti Surabaya in learning English? How are the English teaching and learning materials for the accounting students at SMK Tri Guna Bhakti Surabaya? In line with the research questions, objectives of this research are to describe the needs of the accounting students at SMK Tri Guna Bhakti Surabaya in learning English and English teaching and learning materials for the accounting students at SMK Tri Guna Bhakti Surabaya. This study will give contributions to SMK Tri Guna Bhakti Surabaya and the students. By knowing the students’ needs in learning English as accounting students, the English teachers of SMK Tri Guna Bhakti Surabaya can identify what programs are needed. They can ensure whether the English materials which are delivered, content of the textbooks, schedules etc., are in line with the needs of the students or not. For students, a learning needs analysis helps students identify where they are in terms of their knowledge, skills and competences, where and what they wish to be and ensure what their goals in learning English as accounting students. By knowing those aspects, the students can increase their motivation in learning English to reach their learning goals. This study focuses on analyzing the needs of the accounting students at SMK Tri Guna Bhakti Surabaya in learning English and English teaching and learning materials for them. This study is limited only to the eleventh grade of accounting students at SMK Tri Guna Bhakti Surabaya. So, the result of this study is only applicable to accounting students of SMK and not applicable to the students of SMA or other programs of SMK. METHODS Based on the research questions and objectives of the study, this research was designed as a descriptive qualitative research. According to Surachmad (2004), “Descriptive research is a kind of research method using the techniques of searching, collecting, classifying and analyzing the data, and the objective is to describe phenomenon” and a qualitative research is a type of research which does not include any calculation or enumeration (Moleong, 1989). This research was designed as a descriptive qualitative research because this study investigated the accounting students’ purposes in learning English and their opinions toward English teaching and learning process in the classroom. Hence, the results were reported descriptively as suggestions to English teachers of SMK Tri Guna Bhakti Surabaya in designing specific materials for the accounting students. In this research, accounting students of SMK Tri Guna Bhakti Surabaya were chosen as the subjects of the study. Those students are eleventh graders. There are about 35 students. Those students were chosen as the subjects of the study because the English teacher and also the researcher consider that those students are active and they are considered that they can represent all the accounting students of SMK Tri Guna Bhakti. Research instrument in this research is the researcher herself. To assist her, she used 2 tools, they are questionnaire and observation checklist. Questionnaire was used to get the accounting students’ opinions toward English teaching and learning process in the classroom and their purposes in learning English as accounting students. This questionnaire was given to the eleventh graders of accounting students at SMK Tri Guna Bhakti Surabaya. There are 20 questions. The classification of the questionnaire can be elaborated as the following: The questionnaire consists of 20 multiple choice questions, each of which has four options. The questionnaire is divided into six parts, those are: 1) Part I (questions number 1 – 5) deals with the students’ opinion about teaching-learning process in the class. 2) Part II (questions number 6 – 10) deals with the teaching materials. 3) Part III (questions number 11 – 13) deals with the teacher’s technique in teaching. 4) Part IV (question number 14) deals with the students’ purpose in learning English. 5) Part V (questions number 15-16) deals with the students’ opinions toward the relationship between the learning materials and their purposes in learning English. 6) Part VI (questions number 17-20) deals with the students’ opinions toward school’s plan in designing an ESP course for accounting students. Meanwhile, the observation checklist is in the form of “yes” and “no” answer. The observation checklist comprises the materials, the students’ responses toward English teaching and learning process in the classroom, the teaching techniques that the teacher used, and the English teaching and learning process. Data are the facts and numbers which become the resources to arrange the information. Meanwhile, the sources of data explain the subject from which the data are obtained (Arikunto, 2002). In this research, the data for the first research question are accounting students’ answers on their purposes in learning English. These data were taken from the result of questionnaire that was given by the reseacher to the students. Meanwhile, the data for the second research question are students’ answers or responses on their opinions toward English teaching and learning process in the classroom. These data were taken from the result of questionnaire and observation checklist. The data of the study were collected through observation checklist and questionnaire. In this case the researcher is an observer. As an observer, she used an observation checklist to observe the English teaching and learning process. The researcher observed the English teaching and learning process from the beginning until the end of the class. Here, the researcher observed a classroom, that is XI Ak-1. The data which were gained from questionnaire were used for finding out the students’ purposes in learning English as accounting students and their.opinions toward English teaching and learning process in the classroom. This questionnaire was given to each student at the end of the teaching-learning process. The students were asked to choose an appropriate answer from the options provided based on their own opinion. The data from the observation checklist are in the form of “yes” and “no” answer. The indicators in the checklist comprise the materials, the students’ responses toward the English teaching and learning process, the teaching techniques that the teacher used, and the English teaching and learning process. The result of the observation checklist will be explained descriptively. Meanwhile, in analyzing the students’ opinions toward English teaching and learning materials and their needs in learning English as accounting students, the researcher used the result of questionnaire. The result of questionnaire was analyzed using percentage. RESULT AND DISCUSSION The Result of Study In this part, the researcher reported the results of questionnaire and observation. Those results are explained as follow. 4.1.1 The Needs of the Accounting Students of SMK Tri Guna Bhakti in Learning English This part focuses on the data collected from questionnaire. The questionnaire was given to the accounting students of XI Ak-1 SMK Tri Guna Bhakti Surabaya. Time allocated in collecting data by using questionnaire was thirty minutes in the classroom. Firstly, before giving each student a questionnaire, the researcher tried to take the students’ attention by asking about their needs in learning English. R: “First of all, I want to ask, what are your needs in learning English as accounting students?” S: “Can communicate in English, miss.. Bisa presentasi pakai Bahasa Inggris.” R:“Okay. So, have you learned to present something in English?” S: “Never.. Biasanya disuruh ngerjain soal-soal aja miss.” After that, the researcher explained about English for Specific Purposes. Students listened enthusiastically. R: “Do you know ESP?” S: “No.....” R: “ESP is English for Specific Purposes. ESP ini ditujukan untuk orang-orang yang ingin belajar Bahasa Inggris sesuai dengan kebutuhan mereka. For example, English for engineering students, secretary, hotel industry, nursing, doctor, and also accounting. So, all of you, as accounting students may learn English in the subject area of accounting. You can learn how to present a paper of finance in an office, how to spell numbers, and anything else about accounting.” S: “Oh... so we learn English about accounting only ya miss..?” R: “Yes, that’s right.” S: “Kalau pelajaran Bahasa Inggris yang sekarang berarti bukan ESP ya miss?” R: “I can not say so, I think the curriculum planners of this school should evaluate the English teaching and learning materials deeply.” Then the researcher asked the students opinions if their school has an ESP courses for them. R: “Do you agree if this school open an ESP course for accounting students?” S: “Agree miss... Jadi enak belajarnya nggak bosen.” Finally, the researcher gave each student a questionnaire and asked them to answer the twenty questions included. The students are asked to choose the best answer, from the four options provided, for each question based on their own opinion. There are four questions from twenty questions in the questionnaire that the researcher used to know the accounting students’ needs in learning English. The results are described as follow: a) The Students’ Needs in Learning English From the total thirty five students, thirteen students or 37.1% stated that they are learning English because they want to be able to communicate in English better. Most of them argued that English is important in this globalization era. Meanwhile, the rest of students or twenty two students or 62.8% stated that they are learning English for very specific purpose, that is, they want to be able to communicate in English well in the subject area of accounting activities. b) English Skills that the Students want to Improve From the total thirty five students, twenty nine students or 80% stated that they want to improve their speaking ability. Meanwhile, seven students or 20% stated that they want to improve their writing skill. Most of the students argued that those skills are very important in accounting. c) The Students’ Difficulties in Learning English From the total thirty five students, fifteen students stated that the difficulty they often faced is they easily get bored in participating English learning in the classroom. Nine students stated that they hardly understand the English materials. Eight students stated that they are not learning English enthusiastically and there were three students who stated that they cannot understand the teacher’s explanation easily. d) The Students’ Opinions toward Teaching Techniques Used by The Teacher The students opinions are vary toward teaching techniques used by their English teacher. Twenty students said that their teacher’s technique in teaching is good. The teaching is not really interesting but still understandable. Fifteen students said that the teaching technique is not really good. The teacher’s explanations are often hard to be understood. In the future, all of the students hope their English teacher will give them more speaking exercises. Especially for speaking materials related to accounting activities. They argued that they want to improve their English speaking skill. e) The Students’ Opinions toward School’s Plan in Opening ESP Courses for Each Study Program All students of XI Ak-1 stated that the school really needs to design an ESP course for accounting students. If the school really provides them an ESP course for each study program, they will really appreciate it. All of those students stated that they do agree with that plan. They argued that the ESP course for accounting students should be scheduled as the regular English class. They also stated that they are sure the ESP course will increase their motivation in learning English and it will help them to reach their learning goal, that is, being able to communicate in English in the subject area of accounting. 4.1.2 English Teaching and Learning Materials for the Accounting Students at SMK Tri Guna Bhakti Surabaya This section presents the data collected from classroom observation which had been done by the researcher and questionnaire which was answered by the thirty five students of XI Ak-1. The results were reported as follow: a) The Students’ Opinions toward English Teaching Materials Used by the Teacher All the students of XI Ak-1 stated that the English teaching materials are from a textbook. That English textbook for accounting students is the same as the English textbook for the other study programs in this school. Moreover, twenty five students said that the English teaching materials are not really related to the accounting study program. Meanwhile, ten students said that all of the materials are not related to the accounting study program. Most of the students said that the English teaching materials are not really good for them as accounting students. Only eight students who stated that they could master the English materials delivered by the teacher. Unfortunately, the rest of the students stated that they can not master the English materials. Furthermore, when they were asked about the relationship between the English materials that they must learn in class and their purposes in learning English as accounting students, twenty students stated that the English materials are totally not related to their purposes in learning English as accounting students. Ten students stated that the English materials are related to their purposes and five students stated that the English materials have a little relationship with their purposes in learning English as accounting students. b) The Students’ Responses toward English Learning Process in the Classroom Eleven students stated that they are not really enjoying the English learning process in the classroom. Fifteen students stated that they rarely enjoy learning English in the classroom. Five students stated that they really love learning English in the classroom. Meanwhile, there are four students who stated that they never enjoy the English learning process in the classroom. From thirty five students, eighteen students argued that the English learning process in the classroom is less effective. Fifteen students said the learning process is effective. Meanwhile the rest of students or two students stated that the learning process is very effective. c) The Students’ Opinions toward School’s Plan in Opening ESP Courses for Each Study Program All students of XI Ak-1 stated that the school really needs to design an ESP course for accounting students. If the school really provides them an ESP course for each study program, they will really appreciate it. All of those students stated that they do agree with that plan. They argued that the ESP course for accounting students should be scheduled as the regular English class. They also stated that they are sure the ESP course will increase their motivation in learning English and it will help them to reach their learning goal, that is, being able to communicate in English in the subject area of accounting. 4.1.2.1 Classroom Observation This part presents the result of classroom observation in XI Ak-1. The researcher did this observation to know the English teaching and learning process in the classroom. The observation was held on Wednesday, 5th June 2013. Time allocated for this observation was 2 x 45 minutes. The class began at 06.40 a.m. The teacher entered the class and the students put their English textbook on the desk. The teacher prepared her teaching materials, laptop, LCD, and projector. Some students tried to help the teacher. There were no students absent on that day. There were 35 students in the class and they were in natural condition. Some students were still talking with their friends and some others were ready to learn. After completing preparation of the materials and media, the teacher began to greet the students and then showed the materials which will be discussed that day by LCD. The teacher created PowerPoint slides about the use of simple past tense. The teacher asked about simple past tense to the students. T: “Do you remember about simple past tense?” S: “Yes... buat menyatakan kejadian masa lalu.” T: “Okay. Very good.” Here, the teacher used English and Bahasa Indonesia in teaching. She tried to get her students attention by giving some questions during her explanation. Her explanation was easy to be understood. She spoke loudly but not too fast. She stopped explaining every a few minutes to give her students opportunities to ask. During the teaching learning process, some students seemed like they were sleepy and began to get bored. They laid their head on the table. Some others asked questions actively. The teacher tried to get the students attention by explaining materials with louder voice. After explaining simple past tense, the teacher gave the students time for asking questions. There was nobody ask her about the materials. She then asked her students to make a note about simple past tense on their book. T: ”Silahkan dicatat dulu. If I give you the copy of the slides, maybe you will not read it at home.” S: “Hehehe.... Iya bu.” T: “If you have finished, I will provide you some exercises.” S:”Lhoalahh.... buat PR aja lho bu.” When the students have finished writing their note, the teacher then provided the students some exercises about the use of simple past tense. Some students did it enthusiastically but the rest of students seemed like they were not really wanted to finish the exercises. Twenty minutes left. The teacher walked around the classroom and helped the students in doing the exercises. Then the bell rang. The teacher asked the students to finish the exercises at home and submit it on the next meeting and finally, the class was ended. Discussion This section discusses all the facts which were found by the researcher and their relationship with several related literature provided in Chapter II and the experts’ opinions and suggestions. 4.1.3 The Needs of Accounting Students in Learning English According to the result of questionnaire, most of the accounting students of XI Ak-1 stated that their need in learning English as accounting students is being able to communicate in English, especially English for accounting. In addition, the accounting students stated that they want to improve their English speaking and writing skills in the subject area of accounting. For example, they want to master English vocabularies of accounting, such as credit memo, credits, current assets, cost of goods sold, etc,. They argued that their motivation in learning English will increase when their English materials are related to their study program. If so, they have not to learn all the things which are too general and they do not need even want it. It is in line with the statement that adults learn better when they can see a reason why they are following a program of study and find the relevance between their needs in learning and the content of the study that they must learn. Moreover, as stated by Brindley (1984), “The term need is not as straightforward as it might appear, and hence the term is sometimes used to refer to wants, desires, demands, expectation, motivations, lacks, constraints, and requirements”. In this case, the researcher can conclude that the needs of the accounting students of SMK Tri Guna Bhakti are the more specific English teaching and learning materials and also the more English speaking and writing materials and exercises which are related to their study program, that is accounting. 4.1.4 The English Teaching and Learning Materials for the Accounting Students at SMK Tri Guna Bhakti Surabaya The opinions of the accounting students are vary toward the English teaching and learning process. More than a half of those students stated that the English teaching and learning process is not really effective. The students further argued that it is because the materials provided in the English class are not relevant with their study program and especially with their learning goals. Furthermore, from the result of classroom observation, the researcher found that English textbook used is the same for all study programs in this school. In this school there are two study programs, accounting and office administration. Those students have to learn the same English materials even though they are following different study programs. It is contrast with the fact that learners’ needs are significantly different. Each student has different knowledge, learning style, and also needs. Teachers must know deeply about their students’ characteristics and try to design an appropriate teaching and learning process for them. Here, the English teachers, actually, should prepare or write their teaching and learning materials themselves or in a team based on their learners needs and as the learning provider, the curriculum planners of SMK Tri Guna Bhakti Surabaya have to analyze what the students’ needs in terms of English learning carefully and deeply so that they can address those needs in an appropriate and relevant English teaching and learning materials. Moreover, according to Hutchinson (1987), “Materials writing is one of the most characteristic features of ESP in practice”. In contrast with general English teaching, a large amount of the ESP teachers’ time may be taken in writing materials. Here, in writing and providing appropriate English teaching and learning materials for accounting students, Jones (2012) provides a suggestion for ESP teachers of accounting students. He suggested the instructors in the accounting department of the institution should become close working partners with the ESP instructor to share information about the students’ needs for English and the ways students will use the English when they are learning accounting. The ESP teacher may ask the instructors for samples of English language materials used in accounting teaching: textbooks, research articles, and, if possible, class handouts and sample exercises. It may be useful for the ESP teacher to look at copies of old exams and materials which students used in secondary schools, if they are available. These can be adapted and used in the ESP class to reinforce what is taught in the content area classes. Jones further suggests, “Ask the subject-matter teacher to show you any equipment and laboratory facilities used by the students. Spend some time in the laboratory to determine first-hand the kinds of interactions that are important to the students in their acquisition of English” Based on those explanations above, it is clear that accounting students of SMK Tri Guna Bhakti Surabaya do not find any relevance between the English teaching and learning materials provided to them and their needs in learning English as accounting students. Those students need a more specific English material and class, that is, English for Specific Purposes course for accounting students. According to the answers of those students in questionnaire, they will fully appreciate and support the plan of the curriculum planners of their school in designing English for Specific Purposes course for each study program, especially for accounting students. CONCLUSION AND SUGGESTION Conclusion According to the results of this study, the researcher can conclude that the accounting students of SMK Tri Guna Bhakti Surabaya do not find any relevance between the English maerials that they have to learn in the class and their needs in learning English as accounting students. Their need in learning English is being able to communicate in English well in the subject area of accounting but unfortunately, their English learning materials are not related to the accounting study program. It means that they are still provided with general English learning materials. Suggestion After considering the results and the conclusion of this needs analysis, the suggestion is given to: The English Teachers of SMK Tri Guna Bhakti Surabaya The English teachers of this school have to provide their students with relevant English learning materials. They should know whether their English materials which are provided to the students are related to the study program and their students’ needs in learning English or not. REFERENCES Arikunto, and Suharsimi. 2002. Prosedur Penelitian, Suatu Pendekatan Praktek. Jakarta: Rineka Cipta. Brindley, G. 1984. Needs Analysis an Objective Setting in the Adult Migrant Education Program. Sydney: N.S.W Adult Migrant Service. Burnett, L. 1998. Issues in Immigrant Settlement in Australia. Sydney: National Centre for English Language Teaching and Research. Conelly, E.M and D.J Clandinin. 1988. Teachers as Curriculum Planners. New York: Teachers College, Columbia University. Elley,W. 1984. Tailoring the Evaluation to Fit the Context. The Second Language Curriculum. New York: Cambridge University Press. Gilleard, J., & Gilleard, J.D. 2002. Developing Cross-Cultural Communication Skills. Journal of Professional Issues in Engineering Education and Practice, 128, 187–200. Hutchinson, T., and A. Waters. 1987. English for Specific Purposes. New York: Cambridge University Press. Jones. 2012. English for Accounting Students (http://collections.infocollections.org/ukedu/en/d/Jm0031e/4.2.html) Kaewpet, C. 2009. A Framework for Investigating Learner Needs: Needs Analysis Extended to Curriculum Development. Electronic Journal of Foreign Language Teaching. 2009, Vol. 6, No. 2, pp. 209–220. Linse, C.T. 1993. Assessing Student Needs. In Richards, J.C. 2001. Curriculum Development in Language Teaching. New York: Cambridge University Press. Moleong, Lexy. J. 1980. Metodologi Penelitian Kualitatif. Bandung: PT. Remaja Rosdakarya. Richards, J.C. 2001. Curriculum Development in Language Teaching. New York: Cambridge University Press. Robinson, P.C. 1991. ESP Today: A Practitioner’s Guide. New York: Prentice Hall International. Rodgers, C. 1969. Freedom to Learn. In Hutchinson, T., and A. Waters. 1987. English for Specific Purposes. New York: Cambridge University Press. Shaw, J., and G. Dowsett. 1986. The Evaluation Process in the Adult Migrant Education Program. Adelaide: Adult Migrant Education Program. Surakhmad, Winarno. 2004. Pengantar Penelitian Ilmiah Dasar Metode dan Teknik. Bandung: CV. Trasilo.